Perencanaan Check Dam Penampung Sedimen Di Sungai Jepara Kecamatan Way Jepara Kabupaten Lampung Timur - Nainggolan, Susi Suryanta; Susilo, Gatot Eko; Perangin - Angin, Geleng (Universitas Lampung, 2016)
Jepara watershed is part of the watershed is located in East Lampung district with an area of 10km 2 , where Jepara River is one of river flowing into Lake Jepara. Jepara River conditions at thistime had a reduction in the flow of flood discharge due to reduced cross-sectional area of the riverdue to sedimentation. The main cause of the high rate of sedimentation is the destrusction of watercatchment areas and land management less attention to the principles of conservation land.Therefore it is very necessary management effective river drainage area with emphasis on theconservation and protection of the land and water, especially in the upper reaches of the river.One of the measures for erosion and sedimentastion problem in this river is by building sedimentcontrol structures or so-called check dams.From the calculations have been done check dam is planned to have the following physical;lighthouse spillway crest elevation checkerboard on +35,915 m elevation with an effective heightof 3 m and a depth of 2,5 m foundation,wide spillway lighthouse checkerboard obtained by 40 m,Q design with a return period of 50 years at 119,9113 m3/sec, high wing checkerboard of 2,007 min elevation +39,622 with a height of 0,6 m surveillance, construction of the main dam is aconcrete construstion, lighthouse spillway crest elevation of the sub dam +33,915 m with a heigtof 1 m and a lighthouse foundation depth of 1,2 m, a high wing sub dam at 1,9 m an elevation of +34,4251 m with a height of 1,0 m surveillance, construction of the sub dam is a concreteconstrustion,the elevation of the floor protected at +32,915 m elevation with a thickness of 0,5 m,the construction of a concrete construstion.Keywords : Jepara River, erosion, sedimentation, checkdam